Internalisasi Nilai Ajaran Agama Hindu dalam Membentuk Perilaku Sosial Siswa di SMP Negeri 5 Sukawati Kabupaten Gianyar - I Kadek Agastya Arta Putra; Heny Perbowosari; Putu Ayu Septiari Dewi (Samsara Institute Publisher, 2026)
Students' social behavior is one of the key indicators of the successful implementation of character education in schools. Amid the rapid development of globalization, advances in information technology, and changing patterns of social interaction, various challenges have emerged that contribute to the decline of discipline, responsibility, tolerance, social awareness, and ethical conduct among students. Hindu Religious Education plays a strategic role in instilling moral, spiritual, and social values derived from the teachings of dharma as the foundation for character development. Therefore, the internalization of Hindu religious values constitutes an essential process in shaping students' social behavior through classroom instruction, habituation, exemplary role modeling, and the cultivation of a positive school culture. This study aims to analyze the process of internalizing Hindu religious values in shaping the social behavior of students at SMP Negeri 5 Sukawati, Gianyar Regency, to identify the factors that support and hinder this internalization process, and to describe its implications for students' social behavior. The study employs a qualitative approach using a descriptive research design. Data were collected through observation, in-depth interviews, and document analysis involving the principal, Hindu Religious Education teachers, homeroom teachers, and students as research informants. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, while triangulation techniques were employed to ensure data trustworthiness. The findings reveal that the internalization of Hindu religious values is implemented through the integration of religious values into classroom learning, religious activities, school cultural practices, teachers' exemplary behavior, and family involvement in character development. The values internalized include Tri Kaya Parisudha, Tat Twam Asi, Tri Hita Karana, Ahimsa, and Catur Guru, which are reflected in students' attitudes of mutual respect, discipline, responsibility, cooperation, social concern, and tolerance. The success of the internalization process is supported by the synergy among schools, families, and the community, while the main obstacles include the influence of social media, peer environments, and the lack of consistency in value reinforcement outside the school setting. This study concludes that the systematic and continuous internalization of Hindu religious values effectively fosters students' religious, humanistic, and character-oriented social behavior, thereby providing a viable model for strengthening character education based on Hindu values in the school environment.